Rate of major protein synthesis during the cell cycle of Caulobacter crescentus. - Iba, H (1978)
The rate of major protein synthesis was examined during the synchronous differentiation of Caulobacter crescentus. Total cell proteins were pulse-labeled with [35S]methionine at different times in the swarmer cell cycle and analyzed by sodium dodecyl sulfate- polyacrylamide gel electrophoresis. The rates of synthesis of total cell proteins and of about one-half of the individual major proteins examined increased through G1 and S periods but remained nearly constant during G2 period. The rates of synthesis of the other half of the individual major proteins either increased continuously throughout the swarmer cell cycle or doubled during S period. One stage-specific protein was also detected in late S period. For most of the major proteins examined, the rate of synthesis in the swarmer cell was less than that in the stalked cell. It seemed that, before the onset of G2 period, the Caulobacter cell was already able to synthesize each major protein at the additive rate of the two progeny cells. Compared to the stability of cellular proteins, the functional degradation rate of mRNA coding for individual major proteins was rapid, with half-lives of 0.4 to 5.8 min. It thus seems that the rate of major protein synthesis mainly reflects the transcriptional control of gene expression.